Analysis of outcomes of biliary reconstruction after post‐cholecystectomy bile duct injuries. Issue 7 (28th June 2021) - Anand, Utpal; Kumar, Ramesh; Priyadarshi, Rajeev Nayan; Kumar, Manoj; Kumar, Rakesh; Ahmed, Nehal; John, Aaron George; Parasar, Kunal; Kumar, Bindey
Abstract: Background: Post‐cholecystectomy bile duct injury (BDI) is a serious complication that often requires surgical repair. This study aimed to analyze the outcomes of surgery performed for BDI and to determine the factors associated with post‐surgical complications. Methods: A retrospective analysis was conducted using a prospectively maintained database of 105 patients who underwent surgical repair for post‐cholecystectomy BDI between March 2013 and March 2020. BDI was classified based on the Strasberg‐Bismuth system, and the outcomes were graded using the McDonald criteria. Multivariable logistic regression was used to identify the significant variables associated with postoperative complications. Results: In a cohort of 105 patients with post‐cholecystectomy BDI who underwent bilioenteric repair, 71 (67.6%), 25 (23.8%), 2 (1.9%), and 7 (6.7%) patients had excellent, good, fair, and poor outcomes, respectively, during a median follow‐up of 64 months. The incidence of recurrent biliary stricture after definitive surgical hepaticojejunostomy was 6.7% ( n  = 7). The presence of cholangitis, choledochoduodenal fistula, and hilar biliary strictures was among the significant variables associated with the development of both short‐term and long‐term complications following surgery. Conclusions: Surgical repair of BDIs with bilioenteric anastomosis can yield excellent results when managed in a tertiary care center where expertise in the reconstruction of the biliary tree is prioritized. Abstract : Post‐operative complications following hepatico‐jejunostomy for bile duct injury remain a major concern. Surgical repair of post‐cholecystectomy BDI yields excellent results. On analysis of 105 patients with BDI over a period of 10 years, we found frequent short‐term complications, but recurrent biliary stricture was rare (<7%), and was independently associated with cholangitis and choledochoduodenal fistula. Majority can be managed non‐operatively by percutaneous and endoscopic approach in a tertiary‐care institution.